White line fever - Jones, K. C. (Kevin Charles), 1983- (Tom Doherty Associates, 2025)
"At a passing glance, County Road 951 is an entirely unremarkable stretch of blacktop, a two-lane scar across the Cascade foothills of Central Oregon. But the road is known by another name, coined by locals who've had to clean up after all those scenic detours went horribly wrong: The Devil's Driveway. When Livia and her long-time friends take the Driveway as a shortcut to a much-needed weekend getaway, what begins as a morning joyride quickly becomes anything but. Soon, they're driving for their lives, pursued by a horror beyond anything they ever imagined. The Devil's Driveway might be only 15 miles long, but with danger at every turn, it will take the four women to the very limits of their friendships and their sanity. And there's no telling what else lies in wait just beyond the bend."--Amazon.